The understanding of the spiritual exercises in Karl Rahner and Hans Urs von Balthasar - Boas, Alex Villas (2021)
The purpose of this paper is to make a comparative analysis of the understanding of Saint Ignatius of Loyola’s Spiritual Exercises in two great theologians who influenced theperiod after Vatican Council II in the twentieth century, Karl Rahner (1904–1984) andHans Urs von Balthasar (1905–1988). This analysis aims to identify the image of God asit appears in their respective theological projects, that employing the inductive method,in Rahner’s theological anthropology, and that employing the deductive method, inBalthasar’s theological aesthetics, and to identify how such images of God are involved incontemplative practice according to their respective theological understandings, bothtrying to adapt the Ignatian experience to the contemporary person, each theologian inhis own way. Therefore, this study intends to analyze how the author´s understanding of the Spiritual Exercises is presented within each theological project and then to identifythe similarities and differences between them. Such analysis intends to recognize how these two theologians of great scope understood spirituality first as a part of humanexistence and, in this context, how they understood the knowledge of God as the revela-tion of meaning and the source of new understanding in the search for an authentic life,even given their distinct accents both existential and on the Christian mystical tradition.